PENERAPAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA MASYARAKAT UNTUK MENCEGAH PENULARAN COVID-19 DI WILAYAH KOTA DEPOK - Ardi Pangestu; Azhar Pherdinand Abdillah; Erlangga Sulaeman; Ichsan Al Kautsar; Siti Nur Sehha; Zahira Hananda Naila Rozni (Jurnal Inovasi Penelitian, 2022)
In the condition of the COVID-19 disease outbreak, this is something that must be stopped, namely by means of the community having access to clean water to always wash their hands with soap and not forgetting to increase their immunity, it is recommended to consume fruits and vegetables accompanied by physical activity every days, and for this smoking behavior, because smoking causes damage to the function of the lungs and respiratory tract of humans, it makes it increasingly difficult for COVID-19 sufferers to take oxygen or risk shortness of breath which can be fatal. This study was conducted with the aim of knowing the general description of the state of public health status based on aspects of implementing Clean and Healthy Behavior in the community to prevent the transmission of Covid-19 in the Depok City Region. This study uses a descriptive quantitative method, namely a study conducted to describe a phenomenon. The data presented in the form of numbers in the form of secondary data collection (Depok Health Profile) and primary data collected using questionnaires from June to August 2021 in the Depok City Community. The population in this study was the entire Depok City Community and the sample in this study was as many as 1,018 people in Depok City. The results of this study showed that 550 (54.02%) informants had family members who smoked, this is a factor affected by Covid-19 in the Depok City Area. The conclusion of this study is that Covid-19 is something that must be stopped, namely smoking behavior, because smokers are one of the sufferers who are very at risk of complications and death from the corona virus.